دعوى مخالفة الشيخ محمد بن عبدالوهاب لابن تيمية في مسألة النذر لغير الله - دراسة نقدية –: The Allegation That Shaykh Muhammad Ibn ʿabd Al-Wahhāb Opposed Ibn Taymiyyah on Vows: a Critical Study - Kastriot Mazreku (البصيرة: مجلة الدراسات الإسلامية, 2025)
This study critically examines the claim that Imam Muhammad ibn ʿAbd al-Wahhab contradicted Imam Ibn Taymiyyah regarding the issue of vows (nadhar) made to other than Allah. Opponents of Imam Muhammad ibn ʿAbd al-Wahhab have accused him of diverging from Ibn Taymiyyah, alleging that Ibn Taymiyyah regarded vows made to others besides Allah as either minor shirk (polytheism) or merely a sin, whereas Imam Muhammad ibn ʿAbd al-Wahhab considered them major shirk. The aim of such accusations was to sever the link between the two Imams and to portray Muhammad ibn ʿAbd al-Wahhab as having no scholarly precedent for his call, thereby undermining the reformist movement he led. This study therefore seeks to clarify the alleged divergence between the two Imams on the issue of vows to others besides Allah by analyzing the texts of Ibn Taymiyyah cited by critics, and to demonstrate the consistency between their rulings. The researcher concludes that no real divergence exists between the two Imams concerning this matter, and that Ibn Taymiyyah in fact considered seeking nearness to others besides Allah through vows as major shirk, which fully accords with the position of Imam Muhammad ibn ʿAbd al-Wahhab.